2021
DOI: 10.34172/aim.2021.01
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Geographical Trends of Incidence of Thyroid Cancer in Golestan, Iran, 2004-2013

Abstract: Background: Thyroid cancer is the most common type of endocrine cancer. We aimed to determine the incidence rates of thyroid cancer across a 10-year period (2004-2013) in Golestan, Iran. Methods: We obtained the thyroid cancer data from Golestan Population-Based Cancer Registry (GPCR). Age-standardized incidence rates (ASR) were calculated and reported per 100000 person-years. The Joinpoint software was used to assess time trends, and average annual percent changes (AAPCs) and their corresponding 95% confidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Also, previous data have shown that there has been an increasing trend towards incidence of thyroid cancer (mostly papillary thyroid cancer) in this country over the past decade. [ 9 , 10 ] Therefore, it is important to distinguish between malignant and benign nodules using an accurate diagnostic approach.…”
Section: Introductionmentioning
confidence: 99%
“…Also, previous data have shown that there has been an increasing trend towards incidence of thyroid cancer (mostly papillary thyroid cancer) in this country over the past decade. [ 9 , 10 ] Therefore, it is important to distinguish between malignant and benign nodules using an accurate diagnostic approach.…”
Section: Introductionmentioning
confidence: 99%